Evolution, structure and function of divergent macroH2A1 splice isoforms. (15th February 2023) - Guberovic, Iva; Farkas, Marina; Corujo, David; Buschbeck, Marcus
Abstract: The replacement of replication-coupled histones with non-canonical histone variants provides chromatin with additional properties and contributes to the plasticity of the epigenome. MacroH2A histone variants are counterparts of the replication-coupled histone H2A. They are characterized by a unique tripartite structure, consisting of a histone fold, an unstructured linker, and a globular macrodomain. MacroH2A1.1 and macroH2A1.2 are the result of alternative splicing of the MACROH2A1 gene and can have opposing biological functions. Here, we discuss the structural differences between the macrodomains of the two isoforms, resulting in differential ligand binding. We further discuss how this modulates gene regulation by the two isoforms, in cases resulting in opposing role of macroH2A1.1 and macroH2A1.2 in development and differentiation. Finally, we share recent insight in the evolution of macroH2As. Taken together, in this review, we aim to discuss in unprecedented detail distinct properties and functions of the fascinating macroH2A1 splice isoforms.